(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The areas of application of descriptive analysis to the designs of foreign cultivators for inter-row tillage are considered. The authors performed an analysis of foreign designs of cultivators for inter-row tillage, which shows that there is a tendency to use automatic parallel driving systems. The article establishes that these systems, with the help of sensors, video cameras, computing equipment, monitors, hydraulic system, make it possible to provide a minimum protective zone for plants in a row and increase the working speed of a technological operation, which in turn affects the productivity of the unit, the time of the operation . The authors claim that the use of automatic parallel driving systems on cultivators for inter-row tillage allows reducing the use of herbicides, which is relevant today, as there is a global trend to reduce them and even ban them in some countries. The article reveals the thesis that, based on foreign experience, it is advisable to manufacture domestic cultivators for inter-row cultivation with similar systems of automatic parallel driving, which will enable domestic farmers to use similar equipment.